(untitled) (LACCEI, 2024)
The CDIO methodology has allowed the development of critical and technical-scientific thinking in the graduates of the Aeronautical Engineering program at Universidad Pontificia Bolivariana (UPB), in addition to strengthening research, teamwork, and communication skills. Currently, the program is working on the learning outcomes model following the guidelines of the ABET accreditation model, which requires the creation of capstone-type courses that seek the integration of the learning and skills acquired throughout the students training, when analysing the ABET requirements and the CDIO methodology, common elements were observed that could be applied in the Aircraft Design courses. The way of working and the integration strategy of the CDIO methodology and the capstone course has allowed the courses seen within the study plan not to become isolated themes, but rather to become tools for solving real problems under a project environment that allows the development of new skills such as teamwork, self-learning, design, and problem-solving as close as possible to reality. The results of the implementation strategy and the conclusions that have been observed throughout the implementation of this work modality are presented, which include the motivation of students to carry out different activities such as participating in national and international aircraft design competitions such as the DBF (Design, Build, and Flight) by the American Institute of Aeronautics and Astronautics (AIAA).